THE EXPLORATION OF EFL TEACHING SYLLABUS IN EMANCIPATED CURRICULUM - Saputri, Kurnia; Hadiyanto, Hadiyanto; Sulistyo, Urif; Haryanto, Eddy (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
This study investigates the implementation of the Emancipated Curriculum (Kurikulum Merdeka) in English as a Foreign Language (EFL) instruction, focusing on the alignment between teaching syllabi and the curriculum’s pedagogical vision. The objective of this research is to evaluate the design and structure of teaching syllabi prepared by English teachers, particularly in terms of instructional strategies, assessment practices, and learner-centred approaches. Employing a qualitative method with a case study approach, data were gathered through document analysis of syllabi developed by ten English teachers and supported by semi-structured interviews. Thematic analysis and coding were used to interpret the findings. The results reveal several strengths, including the integration of diverse teaching methods and relevant learning resources. However, the study also identifies notable challenges such as limited interactive classroom activities and a lack of differentiation to support diverse learner needs. The conclusion emphasizes that while the emancipated curriculum holds substantial potential for transforming EFL instruction, its effective implementation requires ongoing teacher development, collaborative planning, and contextual adaptation to ensure its long-term success.